(untitled) (African Disability Rights Yearbook, 2021)
This article gives an account of institutional mechanisms in place for the implementation of the Convention on the Rights of Persons with Disabilities in Tanzania. The protection of human rights depends, among other things, on how effective the institutional mechanisms for the implementation of these standards are. Article 33 of the CRPD provides for domestic implementation, monitoring and consultative mechanisms. Tanzania has in place institution mechanisms for the implementation of disability legislation, which was enacted after the ratification of the CRPD by Tanzania. There are general institutional mechanisms for the monitoring of human rights, which may also be used to monitor specific issues of persons with disabilities. It is a fact that these institutions were in place even before the CRPD. The domestic arrangements in Tanzania for purposes of implementing the CRPD manifest the changing approach, moving away from the old and limited medical/welfare approach to disability, and towards the broader and more inclusive rights approach to disability. The complete change will not be abrupt, because of competing urgent interests, all of which require significant resource mobilisation. Some issues related to law and the disability movement also need to be addressed with a view to enhancing the performance of domestic mechanisms envisaged under article 33 of the CRPD.